Multiple Myeloma: A Recent Update - Vinayachandran , Divya; Siluvai, Sibyl; Kalaivani, V.; Gurram, Prashanthi; Lakshmi Rathan A. C.; Mitthra, Suresh (Advancement and New Understanding in Medical Science Vol. 1, 2024)
We present one such case, where the patient manifested with gross enlargement of the mandible, along with lesions in the lower limbs. A monoclonal gammopathy is often a cause for concern, since it signifies an underlying hematological malignancy. Several systemic diseases initially present with various oral manifestations. Investigation of these oral symptoms may at times lead to the diagnosis of grave underlying life-threatening conditions. A 72-year-old male patient presents to the department with a 10-month history of swelling in the mandible. The swelling had gradually increased in size over time with progressive loss of teeth. These lesions were the initial manifestation and on further investigations the patient was diagnosed with multiple myeloma. Osteolytic lesions including oral and maxillofacial lesions need to be examined carefully, both radiologically and pathologically, to identify cases of multiple myeloma.